1997
DOI: 10.1002/pen.11750
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial, shear, and poisson relaxation and their conversion to bulk relaxation: Studies on poly(methyl methacrylate)

Abstract: Multiple viscoelastic properties were determined for poly(methyl methacrylate) in the context of examining experimental limitations on deriving other properties from these measurements, specifically time dependent bulk modulus behavior. By means of master curves for uniaxial extension on plate and cylinder specimens, as well as shear (torsion) and Poisson behavior from measurements in the temperature range from −40°C to 125°C, it is established that excessive precision is needed for reliable interconversion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…They evidenced an upper plateau at 0.49 for temperatures approaching the glass transition region, while the simultaneously measured creep compliance still displays an increasing trend. Similar results were obtained on amorphous poly (methylmetacrylate) by the group of Knauss [10]. In both the above-cited works the steepest part of the Poisson's ratio isothermal curve is located at temperatures lower than T g .…”
Section: Constant Deformation Testssupporting
confidence: 76%
See 4 more Smart Citations
“…They evidenced an upper plateau at 0.49 for temperatures approaching the glass transition region, while the simultaneously measured creep compliance still displays an increasing trend. Similar results were obtained on amorphous poly (methylmetacrylate) by the group of Knauss [10]. In both the above-cited works the steepest part of the Poisson's ratio isothermal curve is located at temperatures lower than T g .…”
Section: Constant Deformation Testssupporting
confidence: 76%
“…Finally, the data obtained from the Poisson's ratio measured in CDR experiments, shows an intermediate behavior, exhibiting values close to those measured for the moduli functions for temperature up to 40°C, while a deviation is exhibited for higher temperatures, with a slope similar to that shown by the # REL set of data. Previous literature data have always shown that the shift factors required for the Poisson's ratio master curve construction are the same as those obtained for other viscoelastic functions [10,17,20]. The difference found between master curves distribution and between the related shift factors are effects not fully understood, and that could be tentatively ascribed to an interference due to the contact extensometer.…”
Section: Constant Deformation Testsmentioning
confidence: 65%
See 3 more Smart Citations